The woman with a garden : unearthing the artistry and activism of Constance Markievicz 1908-1927 - Caulfield, Mary P. (Trinity College (Dublin, Ireland). Department of Drama, 2011)
Constance Markievicz, one of Ireland's founding figures, would not define herself solely as a journalist nor playwright yet her playtexts and rhetorical outputs were just as much a part of her activism as her military efforts. Markievicz was bom Constance Gore-Booth in 1868. In her short 59 years she proved herself as revolutionary Nationalist, Suffragist, artist, actress and playwright. She was the first woman elected to the British House of Commons though she did not take her seat and along with the other Sinn Fein Teachta Dala (TDs) formed the first Dail Eireann. She was the first woman in Europe to hold a cabinet position (Minister of Labour of the Irish Republic, 1919-1922) and she died from peritonitis in 1927, from working in the Dublin poorhouses.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin